"Not an afterthought": Power imbalances in systemic partnerships between health service providers and consumers in a hospital setting. Issue 8 (August 2018) - Scholz, Brett; Bocking, Julia; Platania-Phung, Chris; Banfield, Michelle; Happell, Brenda
Abstract: Contemporary health policies require consumers be involved at all stages of health service planning, implementation, delivery, and evaluation. The extent to which this policy is met, however, varies widely across the sector. One barrier to meeting policy requirements is power imbalances within systemic partnerships between consumers and other health professionals. Between September 2016 and February 2017, interviews were conducted with health care managers, clinicians, and consumers working on partnerships across various health service departments in one hospital. An exploratory, qualitative approach was used. Data were analysed using principles of discursive psychology, which focuses on the way power is constructed through participants' accounts of partnerships. The findings suggest providers have significant power over consumers in partnerships at the systematic level of health services. Managers were responsible for setting the parameters for partnerships, and consumers were seen more as a resource to be used by health services rather than as equal partners to work with. The findings suggest that although contemporary health policies require partnership with consumers, better guidelines are needed to specifically address and challenge power imbalances within these partnerships.